Meta-analysis of the effectiveness of ethnomathematics-based learning on student mathematical communication in Indonesia - Muhammad Turmuzi; I Gusti Putu Suharta; I Wayan Puja Astawa; I Nengah Suparta (Institute of Advanced Engineering and Science, 2024)
This meta-analysis aims to determine the effect of ethnomathematics learning on students’ mathematical communication skills. Data from 28 research studies, including sample size, standard deviation, mean for both experimental and control groups, and other information, were collected using descriptive analysis. Data analysis techniques used meta-analysis on forest plots, with analytical techniques including heterogeneity testing, calculation of effect sizes, calculation of summary effects using random effects models, and identification of publication bias. The results showed that ethnomathematics-based learning improves students’ mathematical communication skills. The effectiveness of ethnomathematical and conventional learning on students’ mathematical communication skills is combined reliably. The effect size of ethnomathematical learning was 0.97 (95%-CI: 0.74; 1.20). Ethnomathematics-based learning is more effective when compared to traditional.